Pengaruh Daya Tarik Iklan Pantene di Media Sosial (Youtube) terhadap Minat Beli Konsumen - Rafiqa Maulidia; Nurmaningsih Nurmaningsih; Novia Eka Nissrina (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This study aims to determine whether there is an influence of the Attraction of Advertisements on Social Media (Youtube) on Consumer Purchase Interest. The research method used is a quantitative method with a purposive sampling technique. The data collection technique was carried out using a questionnaire method by distributing questionnaires via Google Form. The population of the study was respondents who had watched the Pantene advertisement version of Miracles Hair Supplement with a total of 100 respondents from the calculation results using Rao Purba. The theory used in this study is the S-O-R theory (Stimulus, Organism, Response). The results of this study are the influence of the Attraction of Advertisements on Social Media (Youtube) on Consumer Purchase Interest with a significance value of 0.000 <0.05 and a calculated t value> t table of 3.889> 1.985. In accordance with the S-O-R Theory (Stimulus-Organism-Response) used, the Stimulus, namely the Attraction of the Pantene Advertisement version of Miracles Hair Supplement, has an Attraction so that the audience of the advertisement does Organism, namely attention, understanding, and acceptance. And finally, the audience will make a Response, namely a change in attitude to make a product purchase.